Peran General Store Section dalam Mendukung Mutu Pelayanan Usaha Hotel - Nurjanah, Ita; Putri, Yuliani; Hermawan, Hary (Sekolah Tinggi Pariwisata AMPTA, 2019)
General Store is one of the important sections in Hotels that are included in accounting Deparment. The general store is a storage place for all operational items of the hotel. Each hotel makes its own eforts to keep the inventory of the hotel which will become the guest necessities. This research aims to know what eforts are made to maintain the quality of hotel operational goods through the role of general store section at The Phoenix Hotel Yogyakarta. Is in accordance with the standard or does not give special treatment to the operational goods (ignored). The research method used is qualitative descriptive method by collecting data through interview. Interviews were conducted with general store staf, cost control staf, and trainee of food beverage at The Phoenix Hotel Yogyakarta. The results of the research show that The Hotel Phoenix Yogyakarta made positive eforts that can reduce damage to goods stored in the general store and always ensure the goods that come to the guests in good condition, so that guests will feel satisfied.